Dakwah Multidimensi: Transformasi Sosial-Relijius Dewan Dakwah Islamiyah Indonesia (DDII) Perwakilan Sumatera Barat, 1968-2000 - Aksyarina, Meuthia (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
This article examines the strategic transformation of former Masyumi figures in West Sumatra from practical politics to the path of da'wah and community empowerment through the Indonesian Islamic Propagation Council (DDII) from 1968 to 2000. Utilizing historical methods, this research analyzes how DDII responded to post-PRRI challenges and the rise of Christianization by developing multidimensional programs. The findings reveal that DDII's da'wah strategy was not solely focused on oral propagation (bil-lisan) but was also realized through concrete actions (bil-hal) in the health sector—such as the establishment of the Ibnu Sina Islamic Hospital—education—through the revitalization of Thawalib and the founding of Akabah—as well as the massive deployment of preachers to vulnerable areas. While effective in building community resilience, this study also uncovers internal organizational challenges, including a regeneration system hindered by seniority and suboptimal inter-bureau coordination, which potentially affect the organization's future sustainability.